Molecular characterization of bacteriocin loci in Lactobacillus plantarum I-UL4 - Tai, Hui Fong (2013)
Bacteriocin is a group of proteinaceous antimicrobial peptides produced inhibiting the growth of closely related bacterial strains. Bacteriocin and bacteriocinogenic Lactic Acid Bacteria (LAB) have received special attention due to their potential applications as biopreservative, therapeutic agent and antibiotic-replacer in livestock animals. Lactobacillus plantarum, a member of LAB is found in various ecological niches with more than 10 types of bacteriocins have been reported for this species. L. plantarum IUL4 isolated from the fermented tapioca exhibits a wide spectrum of bacteriocin activity against Gram-positive and Gram-negative bacteria as well as food-borne pathogens. It was reported to carry two bacteriocin structural genes, plW and plnEF encode for plantaricin W and plantaricin EF, respectively. However, the information regarding the bacteriocin biosynthetic genes for plantaricin W and plantaricin EF such as immunity, secretion and regulatory genes as well as the organisation of the respective bacteriocin loci are not available. Hence, the bacteriocin loci of L. plantarum I-UL4 containing plW and plnEF structural genes were analysed in this study. The presence of 24 selected plantaricin (pln) biosynthetic genes (structural, immunity, secretion and regulatory genes) described for plnS, pln423, plW and plnEF loci were amplified and sequenced. The result revealed the presence of eight pln genes and two pln genes from plnEF and plW locus,respectively. On the contrary, the pln genes of plnS locus, pln423 locus and nine pln genes of plnEF locus were absent from the studied strain as confirmed by gradient PCR. The DNA sequence of the flanking region of these pln genes were amplified and sequenced. The results revealed two contigs of 2.7 kilobase (kb) (UL4-plW locus) and 17.5 kb (UL4-plnEF locus), respectively. The UL4-plW locus contains three open reading frames (ORFs) arranged in the same orientation which showed remarkable DNA (≥99.7%) and amino acid (≥99.3%) sequence identities to the plW locus of L. plantarum LMG2379. On the contrary, 21 ORFs were predicted on the UL4-plnEF locus. Each ORF has remarkable DNA and amino acid sequence identities to the reported ORFs of plnEF loci in L. plantarum C11, WCFS1, V90, J51, NC8, J23 and JDM1 (reported plnEF loci). Five operons were deduced in the UL4-plnEF locus: orf345, plnLR, plnUL4IF-UL4HK-plnD, plnEFI and plnGHSUVW. The UL4-plnEF locus was demonstrated to contain different number of bacteriocin gene exhibiting different organisations from the reported plnEF loci. Specifically, plnF (bacteriocin structural gene encoding plantaricin EF) of the UL4-plnEF locus showed mutation which contributed to a longer plnF peptide with isoelectric point was 0.28 lower than the plnF of the reported plnEF loci. Interestingly, the UL4-plnEF locus was shown to be a hybrid of the plnEF locus of L. plantarum JDM1 and J51, where the left-half and right-half of UL4-plnEF locus resembled the plnEF locus of L. plantarum JDM1 and J51, respectively. Southern hybridisation with specific DNA probe showed that both UL4-plW and UL4-plnEF loci were chromosomally encoded. The UL4-plW locus encoded lantibiotic plantaricin W, while the UL4-plnEF locus encoded class IIb plantaricin EF and a putative two-peptide plantaricin orf34. In conclusion, the concurrent presence of the UL4-plW and the mosaic UL4-plnEF loci suggested that the L. plantarum I-UL4 was a novel multi-bacteriocinogenic LAB.